Innovative Machining Strategies for Metal Matrix Composites: Trends and Future Prospects - Olugbenga Ogunbiyi; Tamba Jamiru; Samson Olaitan Jeje; Kazeem Oladiti Sanusi; Mxolisi Brendon Shongwe (Advances in Materials Science and Engineering, 2025)
Metal matrix composites (MMCs) have become increasingly crucial in high-performance applications due to their superior properties like outstanding wear resistance, high specific strength, and low thermal expansion. This review comprehensively examines the machining of MMCs, focusing on both conventional and nonconventional techniques. Conventional methods, including turning, milling, drilling, and grinding, are discussed alongside their inherent challenges and limitations. Nonconventional methods such as abrasive water jet machining (AWJM), ultrasonic machining (USM), electrical discharge machining (EDM), electrochemical machining (ECM), and laser beam machining (LBM) are evaluated for their effectiveness in overcoming these challenges. Recent advances and emerging trends in the field are highlighted, with particular emphasis on hybrid machining techniques, nanomachining, micromachining, and the integration of additive manufacturing with machining processes. The transformative role of artificial intelligence (AI) and machine learning (ML) in process optimization is explored, showcasing improvements in precision, tool wear reduction, and surface quality. Additionally, the review addresses the growing importance of sustainability and green machining practices, underscoring the need for environmentally friendly manufacturing approaches. The paper identifies current challenges in machining MMCs, such as tool wear, process instability, and the complexity of modeling MMC behavior. Innovations needed to overcome these challenges are discussed, including the development of advanced tool materials, coatings, and enhanced modeling techniques. Potential areas for future research are proposed, emphasizing the need for continued exploration of nano-enhanced MMCs, multiscale modeling, and the integration of AI-driven process controls. In conclusion, this review provides a detailed overview of the state of the art in MMC machining, highlights significant advancements, and offers recommendations for both practitioners and researchers to drive future innovations in the field.